2021
DOI: 10.3389/fpsyg.2021.740026
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Relationship Between Parenting Styles and Interpersonal Personality in Chinese Adolescents

Abstract: This study examined the reciprocal relations between the parenting styles and adolescents' interpersonal personality in China. A total of 722 sixth-grade Chinese junior high school students reported their interpersonal relatedness (IR) personality trait and perceived parenting styles of their parents. Of these students, 411 completed the survey again in eighth grade. One parent of each student rated their parenting styles. The results indicated that perceived paternal rejection negatively predicted adolescents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 79 publications
(112 reference statements)
1
4
0
Order By: Relevance
“…Emotional instability, a personality type, was found to have a significant correlation with maternal/paternal criticism and rejection--the characteristics of authoritarian parenting style--in which the level of influence between maternal and paternal rejection varies in the stages of adolescence. Criticism and rejection by mothers were proven to associate with emotional instability in early adolescence (11)(12)(13) while those by fathers were related to emotional instability in middle adolescence (14)(15)(16)(17). This finding justifies previous studies concerning the relationship between authoritarian or neglectful parenting approaches and internalizing and externalizing problems.…”
Section: Parenting and Factors Related To Personality Developmentsupporting
confidence: 72%
See 1 more Smart Citation
“…Emotional instability, a personality type, was found to have a significant correlation with maternal/paternal criticism and rejection--the characteristics of authoritarian parenting style--in which the level of influence between maternal and paternal rejection varies in the stages of adolescence. Criticism and rejection by mothers were proven to associate with emotional instability in early adolescence (11)(12)(13) while those by fathers were related to emotional instability in middle adolescence (14)(15)(16)(17). This finding justifies previous studies concerning the relationship between authoritarian or neglectful parenting approaches and internalizing and externalizing problems.…”
Section: Parenting and Factors Related To Personality Developmentsupporting
confidence: 72%
“…The cultural variation is further discussed in another study [17]. They investigated parenting practices' interaction with adolescents' interpersonal personalities in the Chinese context.…”
Section: Cross-cultural Differences Of This Relationshipmentioning
confidence: 99%
“…To some extent, these parenting styles, along with other household factors, such as the school environment, relation with peers and individual traits such as personality and social skills, determine the individual’s behaviour [ 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the importance of parental parenting style on children's and adolescents' cognitive development ( 17 , 18 ), we have enough reasons to believe the impact of parental parenting style disparities on children's and adolescents' mental health. Second, many previous studies had identified the strong effect of parental characteristics on their children's mental health ( 19 , 20 ). There were also some studies, which supported that mother played more important roles on children's mental health ( 21 23 ).…”
Section: Introductionmentioning
confidence: 99%